Greek to Latin: frameworks and contexts for intertextuality - Hutchinson, G. O. (Oxford University Press, 2013)
The relationship between Latin and Greek literature is one of the most fundamental questions for Latin literature, and for those who study the reception of ancient Greek, and this innovative volume shows some of the contexts in which the interaction of the literatures should be viewed. Hutchinson investigates Roman conceptions of their own literary history and Greek literary history as two chronological sequences, artificially separated, and takes the reader around the Mediterranean to see the different places where Romans encountered Greek art with words. The volume looks at Roman perceptions of the contrasting Greek and Latin languages and compares in detail Latin adaptation of Greek writing with Latin adaptation of Latin, and views the different approaches to Greek material, ideas, and works between three prose 'super-genres', and within the poetic 'super-genre' of hexameters. Based on an independent collection of evidence, it draws extensively on inscriptions, archaeology, papyri, scholia, and little-known texts